1990
DOI: 10.1007/bf01281545
|View full text |Cite
|
Sign up to set email alerts
|

Possibilities of filter-refining of metals and the required characteristics of the filter elements: A review

Abstract: The level of the physical and mechanical properties of steels and alloys can be improved by decreasing the degree of their contamination with nonmetallic inclusions. Among the methods and the technological routes available for solving this problem, the filter-refining method appears to be promising. This method involves passing a molten metal through a filtering unit in which the particles of the nonmetallic phase are separated out and are arrested at the developed surface of the filter. This concept is not ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 9 publications
(19 reference statements)
0
8
0
Order By: Relevance
“…Kondrat'ev et al [29] suggested the formation of a slag-like film at the filter/steel interface, followed by the formation of a reactive zone. Non-metallic inclusions deposited from the melt altered the composition of that slag film and the reactive zone.…”
Section: In Situ Layers Buildupmentioning
confidence: 99%
“…Kondrat'ev et al [29] suggested the formation of a slag-like film at the filter/steel interface, followed by the formation of a reactive zone. Non-metallic inclusions deposited from the melt altered the composition of that slag film and the reactive zone.…”
Section: In Situ Layers Buildupmentioning
confidence: 99%
“…Ceramic foam filters used for the filtration of aluminum and aluminum alloys are typically made of alumina (Al 2 O 3 ) or silicon carbide (SiC) [ 1 ]. In comparison, for the filtration of steel melts, ceramic foam filters predominantly based on zirconia (ZrO 2 ) or carbon bonded alumina (Al 2 O 3 -C) are industrially applied [ 2 ]. Al 2 O 3 -C is a refractory material with a low thermal expansion, negligible sinter shrinkage and improved slagging resistance caused by the low wetting (high contact angle) between carbon-bonded alumina and metallic melts.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14][15] Steel melt filtration is a promising method to remove these last detrimental inclusions prior to casting. [5,[16][17][18][19][20][21][22][23][24] Commonly, ceramic filters are produced by the so-called replication technique.…”
Section: Introductionmentioning
confidence: 99%
“…These very fine inclusions are able to coagulate in the mold to larger clusters of critical sizes in the worst case . Steel melt filtration is a promising method to remove these last detrimental inclusions prior to casting …”
Section: Introductionmentioning
confidence: 99%